2019
DOI: 10.1038/s41591-019-0584-2
|View full text |Cite
|
Sign up to set email alerts
|

A rectal cancer organoid platform to study individual responses to chemoradiation

Abstract: He was a co-founder of Seragon, purchased by Genentech/Roche in 2014. J.M. is a science advisor and owns company stock in Scholar Rock. H.C. is an inventor on several patents related to organoid technology. S.W.L. is a co-founder and scientific advisory board member for ORIC Pharm, Blueprint, and Mirimus. He also serves on the scientific advisory board for Constellation, Petra, and PMV and has recently served as a consultant for Forma, Boehringer Ingelheim, and Aileron. J.G.-A. has received support from Medtro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
375
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 393 publications
(434 citation statements)
references
References 42 publications
18
375
3
Order By: Relevance
“…For the 5FU and FOLFIRI treatments in 3D setting, N and T scaffolds were repopulated with 2.5 × 10 5 HT29 and HCT116 cells in 24-well plates. The FOLFIRI chemotherapy cocktail ratio used was as follows: 5FU:leucovorin:irinotecan, 25:5:1 [52]. Five days post-seeding, the cells were treated with 1 µM, 10 µM, and 100 µM 5FU for 72 h. For the 5FU treatment of 2D cultures, HT29 and HCT116 were seeded at 5 × 10 3 cells per well in 96-well plates and treated with different concentrations of 5FU from 0.1 µM to 100 µM for 72 h. Cell viability was determined 24 h, 48 h, and 72 h post-treatment by reading the absorbance using the Multilabel Plate Reader VICTOR (PerkinElmer, Waltham, MA, USA).…”
Section: Drug Treatment and Cytotoxicity Assaymentioning
confidence: 99%
“…For the 5FU and FOLFIRI treatments in 3D setting, N and T scaffolds were repopulated with 2.5 × 10 5 HT29 and HCT116 cells in 24-well plates. The FOLFIRI chemotherapy cocktail ratio used was as follows: 5FU:leucovorin:irinotecan, 25:5:1 [52]. Five days post-seeding, the cells were treated with 1 µM, 10 µM, and 100 µM 5FU for 72 h. For the 5FU treatment of 2D cultures, HT29 and HCT116 were seeded at 5 × 10 3 cells per well in 96-well plates and treated with different concentrations of 5FU from 0.1 µM to 100 µM for 72 h. Cell viability was determined 24 h, 48 h, and 72 h post-treatment by reading the absorbance using the Multilabel Plate Reader VICTOR (PerkinElmer, Waltham, MA, USA).…”
Section: Drug Treatment and Cytotoxicity Assaymentioning
confidence: 99%
“… 65 Two studies used epithelial organoids derived from patients with rectal cancer to investigate clinical guideline-based chemoradiation treatment. 66 , 67 Both groups concluded that patient-derived organoids reliably predicted the primary tumor response, providing hope that organoids will provide a novel way to better individualize a patient’s treatment regimen.…”
Section: Methodsmentioning
confidence: 99%
“…Using these parameters, the in vitro responses could predict clinical responses with an impressive area under the curve (AUC) of 0.88 and an accuracy of 84%. In the other study, Ganesh and colleagues (Ganesh et al 2019 ) established 65 PDO lines from rectal cancer to test responses to neoadjuvant chemoradiation therapy, including the standard FOLFOX chemotherapy and radiation. The PDO responses significantly reflected the patients’ progression-free survival.…”
Section: Organoids For Translational Researchmentioning
confidence: 99%